Habermas Contra Lyotard: The Question of Modernity - Endut, Ramze (Journal of Ecohumanism, 2024)
This paper will explore the discourse between Jürgen Habermas and Jean-François Lyotard regarding their interpretations of modernity. Both philosophers are significant figures in contemporary thought. Habermas is recognized as a leading critical theorist, while Lyotard is identified as a prominent postmodernist. Despite their differing philosophical frameworks, both acknowledged the increasing complexity of society. In their exchange, Habermas advocated for the concept of universal emancipation, viewing modernity as an ongoing endeavor. Conversely, Lyotard outright dismissed this notion, arguing that Habermas’s perspective represents yet another grand narrative that has lost its validity in the context of postmodernity. Consequently, this paper will analyze the positions of both philosophers, focusing on Habermas’s critique of Lyotard’s postmodernism in relation to modernity.